2018
DOI: 10.4103/ijdvl.ijdvl_744_16
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin's lymphoma arising in a case of mycosis fungoides: An unusual association

Abstract: Mycosis fungoides is a cutaneous T-cell lymphoma with a high risk for developing secondary malignancies, especially B-cell lymphoproliferative disorders. About 40 cases of Hodgkin's lymphoma associated with mycosis fungoides have been reported in literature till date. We report a case of a 35-year-old gentleman who presented with intensely itchy reddish lesions all over the body. Multiple skin biopsies taken from the lesions on scalp and back confirmed the clinical diagnosis of mycosis fungoides. While on trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It has been suggested that MF patients are at higher risk of developing other malignancies, especially haematological ones such as B-cell non-Hodgkin’s lymphomas [ 1 , 2 ], melanoma [ 1 ], lung [ 3 ], colon [ 3 ], and urinary tract cancers [ 1 ], compared to healthy individuals. However, the increased risk of these neoplasm can be related to exposure to chemical carcinogens (chemical-related cancers, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that MF patients are at higher risk of developing other malignancies, especially haematological ones such as B-cell non-Hodgkin’s lymphomas [ 1 , 2 ], melanoma [ 1 ], lung [ 3 ], colon [ 3 ], and urinary tract cancers [ 1 ], compared to healthy individuals. However, the increased risk of these neoplasm can be related to exposure to chemical carcinogens (chemical-related cancers, e.g.…”
Section: Introductionmentioning
confidence: 99%